Application of modified river health index for Sungai Penchala / Sathis Venkitasamy - Sathis , Venkitasamy (2020)
The aim of this study is to have a tool of management of an urban river. A simple tool in terms of index aimed to be developed to manage urban river to meet its intended usage. River Health Index (RHI) developed by combining both physico-chemical parameters and biological measures through scores and weightages. Sungai Penchala is the small urban river chosen for this study. Water quality study, which include physico-chemical parameters, benthic macroinvertebrates and surrounding land use activities have been carried out since May 2016 to September 2016. Ten sampling points have been selected to represent the condition of the river from upstream to downstream. WQI used to represent physico-chemical status of river while Average Species per Taxon (ASPT) value reported for biological water quality condition. Residential, commercial, industrial and mixed type of anthropogenic activities recorded at Sungai Penchala. Average WQI value of Sungai Penchala reported at 58. ASPT score of Sungai Penchala ranges from 2.2 to 5.1. Study findings showed that the Water Quality Index (WQI) and ASPT of Sungai Penchala has a significant positive Spearman rank correlation (0.857, p<0.05). This suggests biological monitoring can be carried out together with physico-chemical monitoring to study river health. RHI in this study required some modification during its development by adapting and simplifying an established framework. Station 1 reported ‘Good’ RHI while Station 4 reported ‘Poor’ RHI. RHI developed can be used to serve as one among earliest integrative indicators in monitoring and reporting the river health in our country.